Hubungan Teknik Mengedan Dan Berat Badan Bayi Baru Lahir Dengan Kejadian Ruptur Perineum Pada Persalinan Normal Di Bidan Praktik Mandiri (BPM) Hirawati, S.Keb.Bd. Desa Simpang Balik Kecamatan Wih Pesam Kabupaten Bener Meriah - Widia Utami, Rizki; Yusran, Mawadhah; HS, Nurlaely (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2023)
Rupture perineum is a tear in the perineum area of the mother during normal delivery that can be influenced by several factors, such as the technique of straining and the weight of the new born. According to the World Health Organization (WHO), there are about 2.7 million cases of rupture perineum in women in maternity and are expected to increase to 6.3 million cases by 2050 This study aims to analyze the relationship between straining techniques and new born weight with the incidence of rupture perineum in normal childbirth in Hirawati independent practice midwife (BPM) Simpang Balik, Kecamatan Wih Pesam, Kabupaten Bener Meriah, during the period January 16 to June 15, 2025. This study uses quantitative methods with cross-sectional design and involves 30 respondents selected in total sampling. Data were analyzed using Chi-Square test with P value of 0.001 for the relationship of straining technique with rupture perineum, which means statistically significant (P<0.05). While the relationship between birth weight and rupture perineum showed P value of 0.333, which was not significant P >0.05) These results concluded that straining techniques have a significant effect on the incidence of rupture perineum, while the baby's birth Weight did not have a significant relationship It iS recommended that health workers increase education about the correct straining technique to minimize the risk of rupture perineum during childbirth